Detection of Ethanol Vapor by modification of the electrical conductivity of Tin Dioxide - Huamán, Fernando (1998)
Sintered tin-oxide-based coating have been fabricated for ethanol vapor sensing. After an appropriate annealing process, particles of low coalescence levels were obtained. The vapor detection is based on the surface resistance variation of the coating due to ethanol vapor presenc. A simplified theoretical model based on surface  adsorption of ionized molecules was used in order to explain this behavior. Our data fitted quite well in the range of 10-130 ug/ml.  For vapor concentration in air we found an experimental value of n=0.63 in the electrical conductance relationship G=G0 [v]m